The Novel "The White Tiger" by Aravind Adiga: A Study in the Context of Cultural Encounters - Venkatanarayanan; Babu, Suresh; M. Suresh (The journal of contemporary issues in business and government, 2017)
"The White Tiger," a book by Aravind Adiga, is an authorised work that brilliantly depicts cultural exchanges amongst diverse parts of Indian society. Aravind Adiga is a well-known author in India. Adiga has shown cultural exchanges inside India, and we feel that togetherness is the key to success. The beauty of our country may be found within its wide variety. Actually, our nation has a number of There are several varied cultures in our country, and as a result, there are numerous cultural exchanges. a process that is going place It is well acknowledged that India is a rapidly expanding nation, and in this regard In order to pursue an economic goal, it must first navigate through a series of cultural contacts. Furthermore, in the There is a vast area of India that has been disregarded, and these stupid individuals have benefited from this neglect. been driven to engage in battle with the wealthier members of society In actuality, the Meetings between the 'haves' and the 'have nots' raise a slew of issues in the minds of both parties. readers who are well-versed in the literature under consideration Cultural interactions provide a signal as to the cultural context. Our civilization is characterised by its uniformity. Traditions, norms, conventions, rituals, and so on have all been revealed in this case. to the prism of the present day Interactions with other cultures are constantly related with one's own identity. The author of the book According to the author, the primary focus is on cultural exchanges between two societies: urban and rural. There is an India of Light, and there is an India of Darkness. The book under consideration also depicts Indians. The impact of Western civilization is having an effect on the way society is evolving. It also draws attention to the The difficulty of rural society to keep up with the speed of urban life in India. This is a rural area.India is feeling ignored and impoverished, which has motivated the lead character of the novel to be a woman. new to engage in rebellion, resulting in a variety of cultural conflicts Balram, the major figure, is eventually revealed. Following all social and economic norms, the main character becomes a successful entrepreneur Indian customs and traditions In this piece of writing, an effort has been made to provide a variety of viewpoints. Episodes of cultural contacts, as depicted by the author, are presented without any type of context. Any emotional propensity towards a certain direction, no matter what it may be.